EFEKTIVITAS PROGRAM KELURAHAN TANGGUH BENCANA DALAM PERSPEKTIF CAPACITY BUILDING - Ulum, Mochamad Chazienul; Kamila Nasution, Nisrina Salma (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2026)
Effectiveness of Kelurahan Tangguh Bencana Program from a Capacity Building Perspective. The establishment of in Disaster-Resilient Urban Area (Kelurahan Tangguh Bencana, KTB) Indonesia offers hope for communities to enhance preparedness in facing frequent disasters. The urgency of the KTB lies in fostering community-based volunteers who are ready and resilient in addressing potential disasters. Community capacity building in disaster management is expected to enhance the ability of communities to cope with disasters. This capacity building is further supported by providing affordable early warning systems and disaster preparedness equipment as part of the program's framework. The aim of this research is to describe and analyze the effectiveness and challenges of the KTB Program from a capacity-building perspective. This study employs a qualitative approach with data analysis using the interactive model by Miles, Huberman, and Saldana, assisted by the NVivo. The finding indicates that the KTB Program in Penanggungan has been effectively implemented from a capacity-building perspective, as evidenced by achieving the eight capacity-building objectives outlined by Chaskin (2001). However, several challenges were identified, including time constraints and dynamic membership changes among human resources, limited budgets, inadequate inter-regional coordination, and the difficulty of altering deeply rooted harmful community habits that could trigger disasters.